Legal Effects of a Notary Deed Read by Notary Staff without Attendance by Notary and Witnesses - Actika, Actika; Wahyuningsih, Sri Endah (TABELLIUS: Journal of Law, 2025)
Abstract. Notaries have an important role in Indonesia, especially in the making of Authentic Deeds, in making Authentic deeds are required to be in accordance with the procedures as regulated in the Notary Law. In the Notary Law, the making of Authentic deeds must be attended or read directly by the Notary concerned and attended by witnesses, but in practice in Indonesia, especially in Batam City, deviations often occur, where in the making of Authentic deeds, for example, in the making of Credit Agreement Deeds at Banks, the reading of credit agreements in the case of credit agreement deeds is only carried out by Notary staff without being attended by Notaries and witnesses. The approach used in this research is a sociological juridical approach. The analysis in this study is prescriptive in nature. The research results concluded: 1) The validity of an Authentic Deed read by a notary staff can be considered legally flawed, and may even not have the power of an Authentic Deed as explained in Article 1869 of the Civil Code and this is also a violation of the law, as a result the deed can be considered formally invalid. 2)The instrumental witness who is not present to witness the process of reading the Authentic deed, in accordance with Article 41 of the UUJN, results in the Authentic deed only having evidentiary power as a private deed, meaning it does not meet the requirements of an Authentic deed. As explained in Article 1868 of the Civil Code, if the formal requirements such as reading in front of witnesses and signing by witnesses are not met, the deed loses its evidentiary power as an authentic deed and the deed only has evidentiary power as a private deed, the value of which is much weaker in legal proceedings and in court.3)Notaries who request to be represented by staff in the reading of authentic deeds may receive administrative sanctions in the form of reprimands, warnings, schorsing (temporary dismissal) from association members, Onzetting (dismissal) from association members, dishonorable dismissal from association membership.Keywords: Instrumental Witness; Notarial Deed; Validity.